Case Report: Characterization of a Novel NONO Intronic Mutation in a Fetus With X-Linked Syndromic Mental Retardation-34 - Sun, Hairui; Han, Lu; Zhang, Xiaoshan; Hao, Xiaoyan; Zhou, Xiaoxue; Pan, Ruiqing; Zhang, Hongjia; He, Yihua (Frontiers in Genetics, 2020)
Background: The NONO gene is located on chromosome Xq13.1 and encodes a nuclear protein involved in RNA synthesis, transcriptional regulation, and DNA repair. Hemizygous variants in NONO have been reported to cause mental retardation, X-linked, syndromic 34 (MRXS34) in males. Due to the scarcity of clinical reports, the clinical characteristics and mutation spectrum of NONO-related disorder have not been entirely determined. Methods: We reported a fetus with hypoplastic left heart syndrome, performed a comprehensive genotyping examination, including copy-number variation sequencing and whole-exome sequencing, and screened for the genetic abnormality. We also conducted an in vitro mini-gene splicing assay to demonstrate the predicted deleterious effects of an intronic variant of NONO. Results: Exome sequencing identified a novel intronic variant (c.154+9A>G) in intron 4 of the NONO gene (NM_001145408.1). It was predicted to insert 4 bp of intron 4 into the mature mRNA. Minigene assay revealed that the c.154+9A>G variant caused the activation of the intronic cryptic splice site and 4 bp insertion (c.154_155ins GTGT) in mature mRNA. Literature review shows that cardiac phenotype, including left ventricular non-compaction cardiomyopathy and congenital heart disease, are consistent features of MRXS34. Conclusion: This study enlarges the mutation spectrum of NONO, further expands hypoplastic left heart syndrome to the phenotype of MRXS34 and points out the importance of intronic sequence analysis and the need for integrative functional studies in the interpretation of sequence variants.